Combined Diabetic Ketoacidosis and Hyperosmolar Hyperglycemic State as the First Presentation of Acromegaly: Case Report and Literature Review - Alshamsi, Shamma; AlSheleh, Hour; Almazrouei, Raya (Journal of Diabetes and Endocrine Practice, 2025)
Acromegaly is characterized by excessive growth hormone secretion and is usually associated with glucose intolerance or diabetes mellitus. It is rare to be associated with life-threatening diabetes emergencies. Here, we present a case of a 38-year-old woman who initially presented with a severe hyperglycemia crisis that meets the criteria for both diabetes ketoacidosis and hyperosmolar hyperglycemic state. Subsequently, she was found to exhibit signs of typical acromegaly, including enlargement of hands, thick skin, and interdental spacing. The diagnosis was established based on typical clinical manifestations, hormonal assays, and radiological findings confirming pituitary macroadenoma. Timely identification and diagnosis are crucial for mitigating the potential complications associated with this condition.
Keywords: diabetic ketoacidosis; acromegaly; hyperosmolar hyperglycemic state; pituitary adenomas